The Influence of Prenatal Counselling on Postpartum Contraceptive Choice - UZUNER, ARZU; AKMAN, MEHMET (FIELD HOUSE PUBLISHING LLP, 2010)
This study tested the hypothesis that individual counselling in the third trimester would increase postpartum contraceptive use to a greater extent than only providing an educational leaflet. A total of 180 third trimester pregnant women of mean age 28.3 years who were attending Marmara University Hospital for prenatal care were enrolled. One-third were randomly allocated to receive prenatal contraceptive counselling and the remaining two-thirds (control group) received an educational leaflet. Participants were followed-up at 6 - 9 months postpartum. The majority of subjects (91.5%) wanted to use contraception after delivery but 26.7% did not know which method to use. At follow-up, 79.6% of all women had begun a postpartum contraceptive regime and 68.7% were using a modern contraceptive method. Overall, there was no statistically significant difference in postpartum contraception use between the control and intervention groups in this study population. It is, therefore, concluded that prenatal counselling was not superior to educational leaflets for increasing the use of effective and modern postpartum contraception.
Keywords: FAMILY PLANNING; CONTRACEPTION; PRENATAL; POSTPARTUM; PREGNANCY; COUNSELLING; INTERVAL; ADVICE; WOMEN